2018
DOI: 10.1186/s12884-018-1779-0
|View full text |Cite
|
Sign up to set email alerts
|

Views on spousal support during delivery: a Turkey experience

Abstract: BackgroundSpousal support is important during delivery since it satisfies the women and their spouses. Thus both women and their spouses should be included, where appropriate, in research on labour and birth. This descriptive study aimed to determine Turkish women’s and their spouses’ views on spousal support during delivery.MethodsThe study population included women who stayed in the postpartum unit of a hospital and gave birth vaginally to their first child between the thirty-seventh and forty-second week of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The mean age of pregnant women was 30.1 ± 5.6 years and their ages ranged between 26-35 years. This was quite similar to a study that revealed that 71.2% of the respondents' age ranged between 20 and 30 years [13] and another study whose respondents' mean age was 34 years [14] .The finding indicated that pregnant women are still in their reproductive age.…”
Section: Socio-demographic Factors Of Respondents (N=398)supporting
confidence: 87%
See 1 more Smart Citation
“…The mean age of pregnant women was 30.1 ± 5.6 years and their ages ranged between 26-35 years. This was quite similar to a study that revealed that 71.2% of the respondents' age ranged between 20 and 30 years [13] and another study whose respondents' mean age was 34 years [14] .The finding indicated that pregnant women are still in their reproductive age.…”
Section: Socio-demographic Factors Of Respondents (N=398)supporting
confidence: 87%
“…This was in line with the outcome of a study reported by [21] It was also reported that 49.9% of the respondents specified that physical support only was the major role that was perceived as needful during pregnancy (21) . 49.7% of the respondents indicated that spiritual support only was the major role perceived to be needful during labour and after delivery while financial support (60.3%) was the major role perceived to be needful in newborn care.Another study revealed that 86% of the respondents specified that they needed emotional support while 14% of them indicated that they needed physical support from their spouses during the period of delivery [13]. Furthermore, a study quoted that different types of spousal support to be given to pregnant women include emotional, physical, financial, spiritual and psychological support during pregnancy, labour, period and after delivery [14].…”
Section: Social Supportmentioning
confidence: 99%
“…The strain in delivery, social distress, and family burden can be a major concern for women [ 36 ], and prevent uptake of SSC. Furthermore, spousal support could in no small measure enhance the uptake of SSC [ 37 ]. For example, in a previous study, husbands whose wives utilized skilled delivery care provided instrumental, emotional, and informational support to their wives during delivery and understood that medical support was paramount in positive childbirth outcome [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Childbirth is an important experience in which parents gain a new role in their lives. Professional assistance during labour can help women feel in control and able to deal with the pain of labour, which can help avoid unwanted childbirth experiences [ 1 ]. A family member, friend, midwife, or partner can offer company and support throughout labour [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A family member, friend, midwife, or partner can offer company and support throughout labour [ 2 ]. The approach of labour companionship was introduced to Türkiye over the last three decades [ 1 ]. Labour companionship by fathers has become an increasingly common practice in resource-rich regions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%